Managing Volunteer Programs: Reporting Volunteer Contributions - Robert R. Meadows; Marilyn K. Lesmeister; Marilyn N. Norman (EDIS)
Volunteers working in community programs make a difference in many neighborhoods, counties, and states. But, the value of a volunteer program is sometimes overlooked. Documenting the value of volunteer programs helps to celebrate success today and promote growth in the future. The manager of a volunteer program is in a good position to monitor and report the success and value of that program. This document is FCS9239, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. Original publication date March 1, 2006.